Silence is golden. Issue 8 (10th July 2018) - Cooke, Georga; Mitchell, Ben
Abstract : Cooke and Mitchell comment on Ott et al.'s findings that hesitation can be interpreted as incompetence and suggest it could instead be thought of as a teaching moment.